Two Birds with One Stone: Using Indium Oxide Surficial Modification to Tune Inner Helmholtz Plane and Regulate Nucleation for Dendrite‐free Lithium Anode. Issue 5 (11th March 2022) - Chen, Yaqi; Xu, Xieyu; Gao, Leiwen; Yu, Guangyong; Kapitanova, Olesya O.; Xiong, Shizhao; Volkov, Valentyn S.; Song, Zhongxiao; Liu, Yangyang
Abstract: Lithium metal has been considered as the most promising anode material due to its distinguished specific capacity of 3860 mAh g –1 and the lowest reduction potential of ‐3.04 V versus the Standard Hydrogen Electrode. However, the practicalization of Li‐metal batteries (LMBs) is still challenged by the dendritic growth of Li during cycling, which is governed by the surface properties of the electrodepositing substrate. Herein, a surface modification with indium oxide on the copper current collector via magnetron sputtering, which can be spontaneously lithiated to form a composite of lithium indium oxide and Li‐In alloy, is proposed. Thus, the growth of Li dendrites is effectively suppressed via regulating the inner Helmholtz plane modified with LiInO2 to foster the desolvation of Li‐ion and induce the nucleation of Li‐metal in two‐dimensions through electro‐crystallization with Li‐In alloy. Using the In2 O3 modification, the Li‐metal anode exhibits outstanding cyclic stability, and LMBs with lithium cobalt oxide cathode present excellent capacity retention (above 80% over 600 cycles). Enlightening, the scalable magnetron sputtering method reported here paves a novel way to accelerate the practical application of the Li anode in LMBs to pursue higher energy density. Abstract : A surface modification with indium oxide on the copper current collector via magnetron sputtering was proposed, which can be spontaneously lithiated to form a composite of lithium indium oxide and Li‐In alloy. Thus, the growth of Li dendrites is effectively suppressed via regulating the inner Helmholtz plane modified with LiInO2 to foster the desolvation of Li‐ions and to induce the nucleation of Li‐metal in two‐dimensions through electro‐crystallization with Li‐In alloy.